Hubungan Dukungan Orang Tua dengan Motivasi Berlatih Atlet Karate Gokasi - Jannah, Miftahul; Susanto, Indra Himawan; Mustar, Yetty Septiani (Jurnal Porkes, 2022)
Parental support is needed to support the success of a child when practicing and competing. The covid-19 pandemic caused athletes to reduce the frequency and duration of their training resulting in a lack of monitoring from coaches and led to a decrease in motivation. This study has the goal of knowing the relationship between parental support and the motivation to train athletes. The study subjects were 20 karate athletes. Data collection through the dissemination of questionnaires in the form of google forms and disseminated online. Data analysis is carried out by looking for the relationship between two variables, namely by using correlation coefficient analysis with the Statistical Program for Social Sciences (SPSS) application version 20 and the level of significance (p value) < 0.05. It is stated that there is a correlation / relationship if the p value > r table and obtained a result of 0.609 > 0.444 so that the relationship of parental support with athlete training motivation falls into the category of strong correlation. This research can be used as a basis related to the determination of the program by the coach and parent's reference that the parent's support in the form of emotional support, appreciation, information, advice, and praise can make the child develop well, have a sense of trust, so that his hopes can achieve the desired achievement.